Evaluation of various specialty protein sources as replacements for spray-dried animal plasma in diets for segregated early-weaned pigs - W B Nessmith Jr; J R Bergstrom; J A Loughmiller; J W Smith II; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1996)
We used high-health status, weanling pigs to evaluate six different protein sources as replacements for spray-dried animal plasma. Spray-dried blood meal, spray-dried egg, spray-dried wheat gluten, extruded soy protein concentrate, select menhaden fish meal, and soybean meal each replaced 2.5 or 5.0% spray-dried animal plasma. Pigs fed increasing levels of spray-dried blood meal, spray-dried egg, or soybean meal had decreased ADFI; however, increasing levels of select menhaden fish meal, extruded soy protein concentrate, and spray-dried wheat gluten had no influence or increased ADFI. For the high-health pigs used in this trial, select menhaden fish meal, extruded soy protein concentrate, and soybean meal appear to be effective in replacing a portion of the spray-dried plasma in the segregated-early weaned (SEW) diet. However, in contrast to other studies, the level of spray-dried animal plasma was not observed to have an effect on SEW pig performance. The conflicting results between this study and past trials in the performance of spray-dried blood meal and spray-dried egg indicate that quality standards should be established for all protein sources.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Protein source; Weanling pigs